Cancer-associated fibroblast-derived exosomal miR-18b promotes breast cancer invasion and metastasis by regulating TCEAL7 - Ziqian Yan (Nature Publishing Group, 2021)
Abstract Studies have shown that cancer-associated fibroblasts (CAFs) play an irreplaceable role in the occurrence and development of tumors. Therefore, exploring the action and mechanism of CAFs on tumor cells is particularly important. In this study, we compared the effects of CAFs-derived exosomes and normal fibroblasts (NFs)-derived exosomes on breast cancer cells migration and invasion. The results showed that exosomes from both CAFs and NFs could enter into breast cancer cells and CAFs-derived exosomes had a more enhancing effect on breast cancer cells migration and invasion than NFs-derived exosomes. Furthermore, microRNA (miR)-18b was upregulated in CAFs-derived exosomes, and CAFs-derived exosomes miR-18b can promote breast cancer cell migration and metastasis by specifically binding to the 3′UTR of Transcription Elongation Factor A Like 7 (TCEAL7). The miR-18b-TCEAL7 pathway promotes nuclear Snail ectopic activation by activating nuclear factor-kappa B (NF-κB), thereby inducing epithelial-mesenchymal transition (EMT) and promoting cell invasion and metastasis. Moreover, CAFs-derived exosomes miR-18b could promote mouse xenograft model tumor metastasis. Overall, our findings suggest that CAFs-derived exosomes miR-18b promote nuclear Snail ectopic by targeting TCEAL7 to activate the NF-κB pathway, thereby inducing EMT, invasion, and metastasis of breast cancer. Targeting CAFs-derived exosome miR-18b may be a potential treatment option to overcome breast cancer progression.